Multi-Level Features Extraction for Discontinuous Target Tracking in Remote Sensing Image Monitoring - Bin Zhou; Xuemei Duan; Dongjun Ye; Wei Wei; Marcin Woźniak; Dawid Połap; Robertas Damaševičius (Sensors, 2019)
Many techniques have been developed for computer vision in the past years. Features extraction and matching are the basis of many high-level applications. In this paper, we propose a multi-level features extraction for discontinuous target tracking in remote sensing image monitoring. The features of the reference image are pre-extracted at different levels. The first-level features are used to roughly check the candidate targets and other levels are used for refined matching. With Gaussian weight function introduced, the support of matching features is accumulated to make a final decision. Adaptive neighborhood and principal component analysis are used to improve the description of the feature. Experimental results verify the efficiency and accuracy of the proposed method.